Isolation and Identification of Ananixanthone from Ethyl Acetate Extract of Root Bark Of Slatri (Calophyllum Soulattri) (Clusiaceae)) - Dindha Ramah Mulia; Nestri Wulandari; Muhammad Widyo Wartono (UNIVERSITAS SEBELAS MARET (UNS), 2016)
A xanthone, named ananixanthone (1) has been isolated and identified from the ethyl acetate extract of the root barks of Calophyllum soulattri. Structure of the compound was determined based on spectroscopic data, including UV, IR, NMR 1D, NMR 2D and by comparison with references.